Rock Concert Performance from ABBA to ZZ Top - Smith, Peter (Lexington Books, 2022)
This book presents an analysis of 100 rock concert performances and attempts to answer the question "What makes a truly great rock performance?" Author Peter Smith, an experienced concert goer, delves into his own recollections of experiencing rock performances over the last 50+ years and, with the support of his daughter, Laura Smith, analyzes 100 selected performances covering the themes of icons, persona, energy, fandom, venues, communities, politics, art-rock, authenticity and maturity. The approach taken is based upon qualitative analysis, reflection, and autoethnography. The selected performances cover a range of diverse acts such as the Rolling Stones, ABBA, Sex Pistols, Barbara Streisand, David Bowie, and the like.